Arduino and Kinect projects Design, build, blow their minds - Melgar, Enrique Ramos (Apress, 2012)
Provides an introduction to Arduino, Kinect and Processing and includes step-by-step instructions for ten projects.
Print version record
Keywords: Arduino (Programmable controller); Kinect (Programmable controller); Multimodal user interfaces (Computer systems); Automatic control -- Computer programs; Three-dimensional imaging; Programmable controllers; computerwetenschappen; computer sciences; software engineering; operating systems; Information and Communication Technology (General); Informatie- en communicatietechnologie (algemeen); Arduino (Automate programmable); Kinect; Interfaces utilisateurs multimodales (Systèmes informatiques); Imagerie tridimensionnelle; Automates programmables; three-dimensional; TECHNOLOGY & ENGINEERING; Engineering (General); Informatique; Automatic control; Computer programs